IMPROVING A MANAGER'S COMMUNICATION SKILLS AS A GUARANTEE OFSUCCESSFUL MANAGEMENT - FEDORYSHYNA, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to substantiate the need to improve the communication skills of a manager as the basis for the formation of his communicative competence and the strategic advantage of the organization in a dynamic environment.A list of the most important skills that will be in demand by employers in the next five years is provided, and the role of communication skills is highlighted. An approach to the development of key competencies of the 21st century is described ‒ the 4K model, which includes four basic skills: critical thinking, creativity, communication and collaboration. It is also substantiated that the primary need for the development of communication skills is for business owners, managers and leaders of change in organizations; public administrators, politicians and public figures; specialists working with clients (including in the field of sales and marketing); participants in the educational process (both teachers and educators, and students at different levels of education).It was determined that the need to develop communication skills in managers of different levels of management is due to the following reasons: effective team management, building trust and image, working in conditions of change, effective interaction with partners and clients, conflict management, promoting innovation and creativity, digitalization. The factors that influence the development of a manager's communication skills (internal and external) are described. Internal (personal) factors are related to the personality of the manager and include: self-awareness and self-reflection, level of emotional intelligence, level of education and culture, character and temperament, motivation for development. External factors include interpersonal, organizational, social and professional factors.Methods that contribute to the development of communication skills and communicative competence of both the manager and the staff are substantiated.It has been proven that developing communication skills of managers not only improves the work of the team, but also becomes a strategic advantage that allows the organization to confidently occupy leading positions in the market, build a reputation as a reliable employer, and attract and retain talent.
Keywords: communication; communication skills; communication competence; manager; management